Prevalence of use of psychoactive substances in pregnancy and knowledge of the effects on the fetus postpartum - Pérez-Franco, Juan; Raffo, Silvia (Revista Chilena de Salud Pública, 2015)
Background: There is a scarcity of records in Chile concerning pregnant women’s knowledge of the effect of psychoactive substance use (PSU) and its impact on abstinence and on the neonate. The present work explored biodemographic data, prevalence of substance use, and the relationship between women’s knowledge about effects on the foetus, abstinence and mental health. Method: 264 postpartum women were asked to fill a questionnaire recording PSU, biodemographic data, newborn outcome measures, and included the 12-item General Health Questionnaire (GHQ-12). Interviews were conducted to determine the level of knowledge concerning the effects of psychoactive substances on the foetus. Results: Cigarettes were the most used substance (11.3% of prevalence at the 9th month). Newborns of smokers who smoked more than 800 cigarettes during pregnancy had a significant lower birth weight. Only alcohol use was reduced in women knowledgeable of its effects on the foetus (t-test = 2.126, p-value = 0.037). GHQ-12 results were different only amongst women that had used cocaine prior to the pregnancy. Discussion: Knowledge of the effects of PSU on the foetus did not impact the decision to abstain from use. It is worrying that this lack of relationship was particularly notable for cigarettes, the most used substance, and the only substance associated with low birth weight.